Risk factors for level V lymph node metastases in solitary papillary thyroid carcinoma with clinically lateral lymph node metastases. (1st July 2016) - Yang, Jing; Gong, Yanping; Yan, Shuping; Zhu, Jingqiang; Li, Zhihui; Gong, Rixiang
Abstract: The extent of lateral neck dissection (LND) in surgical resection of papillary thyroid carcinoma (PTC) with clinically lateral LNM (LLNM) remains controversial. We aimed to explore the frequency of and risk factors for level V LNM in patients with solitary PTC and clinically LLNM. To analyze the frequency and risk factors for level V LNM, we retrospectively reviewed 220 solitary PTC patients who underwent total thyroidectomy, bilateral central neck dissection, and therapeutic LND. LLNM were present in 82.3% patients, and levels II–V LNM were present in 45.9%, 62.7%, 55.5%, and 12.3% patients, respectively. Ipsilateral level V LNM was significantly associated with tumor size >10 mm, extrathyroidal extension, ipsilateral central LNM ratio ≥50%, and contralateral central LNM (CLNM), bilateral CLNM, and simultaneous levels II–IV LNM. Contralateral CLNM was an independent risk factor for level V LNM. In patients with solitary PTC and clinically LLNM, level V LNM was relatively uncommon. Therefore, routine level V lymphadenectomy may be unnecessary in these patients unless level V LNM is suspected on preoperative examination or associated risk factors, especially contralateral CLNM, are present. Abstract : Tumor size >10 mm, extrathyroidal extension, ipsilateral central LNM ratio ≥50%, and the presence of contralateral central LNM (CLNM), bilateral CLNM, and simultaneous levels II–IV LNM were risk factors for level V LNM. And contralateral CLNM was an independent risk factor for level V LNM in solitary PTC with clinically LLNM.